The landscape of 'podoplanin' in dermatology: a narrative review - Nagwa Diab; Magda Assaf; Nourhan Anis; Eman Salah (Wolters Kluwer Medknow Publications, 2021)
Podoplanin (PDPN) is a specific marker for lymphatic endothelial cells; however, it can be expressed by many other cells including renal podocytes. In dermatology, PDPN has been involved in diverse disorders, such as tumor lymphangiogenesis, as well as in immune-mediated disorders. Herein, we illustrate and discuss the landscape of PDPN in dermatology.